Differences and commonalities of plant responses to single and combined stresses. (2nd May 2017) - Zhang, Haina; Sonnewald, Uwe
Summary: In natural or agricultural environments, plants are constantly exposed to a wide range of biotic and abiotic stresses. Given the forecasted global climate changes, plants will cope with heat waves, drought periods and pathogens at the same time or consecutively. Heat and drought cause opposing physiological responses, while pathogens may or may not profit from climate changes depending on their lifestyle. Several studies have been conducted to find stress‐specific signatures or stress‐independent commonalities. Previously this has been done by comparing different single stress treatments. This approach has been proven difficult since most studies, comparing single and combined stress conditions, have come to the conclusion that each stress treatment results in specific transcriptional changes. Although transcriptional changes at the level of individual genes are highly variable and stress‐specific, central metabolic and signaling responses seem to be common, often leading to an overall reduced plant growth. Understanding how specific transcriptional changes are linked to stress adaptations and identifying central hubs controlling this interaction will be the challenge for the coming years. In this review, we will summarize current knowledge on plant responses to different individual and combined stresses and try to find a common thread potentially underlying these responses. We will begin with a brief summary of known physiological, metabolic, transcriptional and hormonal responses to individual stresses, elucidate potential commonalities and conflicts and finally we will describe results obtained during combined stress experiments. Here we will concentrate on simultaneous application of stress conditions but we will also touch consequences of sequential stress treatments. Significance Statement: In natural or agricultural environments, plants are constantly exposed to a wide range of biotic and abiotic stress conditions. In this review, we will summarize current knowledge on plant responses to different individual and combined stress conditions and try to find a common thread potentially underlying these responses.